2015
DOI: 10.3390/antib4010048
|View full text |Cite
|
Sign up to set email alerts
|

Targeting sTNF/TNFR1 Signaling as a New Therapeutic Strategy

Abstract: Deregulation of the tumor necrosis factor (TNF) plays an important role in the initiation and perpetuation of chronic inflammation and has been implicated in the development of various autoimmune diseases. Accordingly, TNF-inhibitors are successfully used for the treatment of several diseases, such as rheumatoid arthritis, inflammatory bowel disease, and psoriasis. However, total inhibition of TNF can cause severe side effects such as an increased risk of inflammation and reactivation of tuberculosis. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 122 publications
0
71
0
1
Order By: Relevance
“…TNFR1 is a major receptor for TNFα, mediates apoptosis, and functions as a regulator of inflammation [21]. Our cellular uptake assay results indicated that TNFα increases the cellular uptake of AgNPs.…”
Section: Resultsmentioning
confidence: 79%
“…TNFR1 is a major receptor for TNFα, mediates apoptosis, and functions as a regulator of inflammation [21]. Our cellular uptake assay results indicated that TNFα increases the cellular uptake of AgNPs.…”
Section: Resultsmentioning
confidence: 79%
“…Further, for neuronal cells, it was shown previously that proper TNFR2 activation induces protection from excitotoxicity in vitro (15,16); in the in vivo model analyzed here, in neurons in the vicinity of the acute insult and not immediately succumbing to excitotoxic death, competition of TNFRs for limiting amounts of endogenously produced membrane form of TNF exists, which results in suboptimal activation of TNFR2 of this cell population under a nontreatment condition. Moreover, at the level of intracellular signaling, it is known that signal cross-talk between TNFR1 and 2 exists in terms of competition for common signal transducers such as TRAF2 (33)(34)(35), with TNFR1 outperforming TNFR2 pathways in the case of abundance of soluble TNF, which triggers exclusively TNFR1 (3,6). In the presence of ATROSAB, neuronal response is shifted toward neuroprotective TNFR2 signaling because of blocked neuronal TNFR1, allowing the induction of a resistant state by endogenous tmTNF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next to induction or aggravation of demyelinating diseases, all anti-TNF therapeutics may induce severe side effects such as serious infections, including reactivation of tuberculosis and invasive fungal and other opportunistic infections. An increased susceptibility to develop additional autoimmune diseases and lymphomas has also been reported (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The major difference between the two receptors has been reported to be the presence of a death domain in TNFR1 and absence of a death domain in TNFR2 [4]. TNF has been found to activate proapoptotic signaling cascade through TNFR1 [5] which is expressed in various types of cells, tissues [6] and tumors [7]. Studies have shown that antibodies against TNFR1 mimic the effect of TNF-α [8,9] and as a result initiate the apoptosis process.…”
Section: Introductionmentioning
confidence: 99%